Social Technocracies: the emergence of a technocracy in the Ministry of Development and Social Inclusion - Vela, Estelí (2014)
This article analyzes the technocracy emergence in social sector, through the study of the Ministry of Development and Social Inclusion case, created in 2011 in response to one of the essential themes of Ollanta Humala’s electoral campaign: social inclusion. This paper aims to determine which factors led to the establishment of a technocracy linked to social policy in a country where it has been traditionally linked to political usage and patronage. There are three factors that explain the positioning of a technocracy in this ministry addressed throughout the article. On one hand, there was the presence of a consensus about the need for a technical management of this sector in the search of generating legitimacy and autonomy. On the other hand, it happened to be a favorable political environment characterized by a wide political support from the government. Finally, the wide discretion of the technical team in the design of MIDIS and during formation of the first ministerial body of bureaucrats allowed the emergence of a technocratic institution. To this end, this article describes development of the stages of the creation of the institution, design, approval and implementation and shows a corroboration of the technocratic profile of the initial top management team of this ministry.